2004
DOI: 10.1113/jphysiol.2004.072306
|View full text |Cite
|
Sign up to set email alerts
|

Cell swelling‐induced ATP release is tightly dependent on intracellular calcium elevations

Abstract: Mechanical stresses release ATP from a variety of cells by a poorly defined mechanism(s).Using custom-designed flow-through chambers, we investigated the kinetics of cell swellinginduced ATP secretion, cell volume and intracellular calcium changes in epithelial A549 and 16HBE14o− cells, and NIH/3T3 fibroblasts. Fifty per cent hypotonic shock triggered transient ATP release from cell confluent monolayers, which consistently peaked at around 1 min 45 s for A549 and NIH/3T3, and at 3 min for 16HBE14o − cells, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
116
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(127 citation statements)
references
References 54 publications
10
116
1
Order By: Relevance
“…Numerous studies have demonstrated that cellular swelling activates a robust and large ATP release [42,[66][67][68]. This coincides with the fact that all cells in general react to cellular swelling with the activation of volume-sensitive anion channels [69].…”
Section: Cell Swelling-activated Anion Conductancementioning
confidence: 66%
See 3 more Smart Citations
“…Numerous studies have demonstrated that cellular swelling activates a robust and large ATP release [42,[66][67][68]. This coincides with the fact that all cells in general react to cellular swelling with the activation of volume-sensitive anion channels [69].…”
Section: Cell Swelling-activated Anion Conductancementioning
confidence: 66%
“…However, mechanically triggered ATP release continues to be present in the absence of pl-VDAC-1 [73]. Another conflicting finding regarding VDAC is its very long lag time before activation of the membrane current (>10 min) [70], a finding which argues against its involvement in swelling-induced ATP release that always occurs promptly [67]. In addition, the other smaller conductance, outwardly rectifying VSOAC, has been suggested to mediate swelling-induced ATP release from endothelial cells.…”
Section: Cell Swelling-activated Anion Conductancementioning
confidence: 99%
See 2 more Smart Citations
“…It will now be important to assess the contribution of VNUT to the release of ATP in other tissues in which evidence of exocytotic release of ATP has been reported, e.g., astrocytes [66][67][68][69][70], hepatocytes [64,71,72], alveolar A549 and intestinal 407 epithelial cells [73][74][75][76][77], osteoblasts [78], and esophageal keratinocytes [40]. It will be also important to biochemically and functionally identify the ATP-rich compartment(s) contributing to VNUT-dependent ATP release from non-endocrine/exocrine cell types exhibiting vesicular release of ATP.…”
Section: Cellular Release Of Nucleotides From the Secretory Pathwaymentioning
confidence: 99%